Educational Implications of the Concept of Desertion in the Holy Quran (Journal Of Educational and Psychological Researches, 2022)
The purpose of the present study is to identify the comprehensive concept of desertion through the Holy Qur’an and to derive some educational implications related to the concept of desertion and its editing. The also aims to explain the images and forms of desertion. The researcher used the qualitative analytical method. The study concluded that the comprehensive concept of desertion was represented in moving from the country of polytheism to the country of Islam, singularity, alienation, and isolation, leaving, repelling and showing off, abandoning the wife in bed, and reciting from the Qur’an recitation, action, and arbitration, insulting, abandoning, delirium, intersection, and manipulation. The researcher has drawn many educational implications from the concept of desertion, which he clarified in the folds of his research.The researcher has recommended that: teachers should strive to clarify the concept of desertion for people through dealing with it, and explain the purpose of it and forbidden. Educators should also be interested in clarifying the concept of desertion and its application methods in schools and with learners. The need to use social media with a view to clarifying the concept of desertion and its applications to the public People. Activating the role of mosques and educational media in spreading cultural awareness regarding the concept of desertion. The creation of an electronic library dealing with semantic concepts contained in the Holy Quran. Directing the attention of teachers to present student projects based on the concept of desertion and its educational implications for learners.